2014
DOI: 10.1177/0143034314560623
|View full text |Cite
|
Sign up to set email alerts
|

Chinese teachers’ perceptions of the roles and functions of school psychological service providers in Beijing

Abstract: This study used a semi-structured interview with 94 teachers from 92 elementary and secondary schools in Beijing, China, to explore their perceptions of the roles, training, and challenges of school psychological service providers (SPs) as well as teachers’ satisfaction with the services provided by SPs. Results indicated that the SP to student ratio was 1:1360. Only 32 (34.8%) schools had SPs who were certified as mental health counselors or who had degrees in psychology, and 18 (19.6%) schools did not have S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 4 publications
0
12
0
Order By: Relevance
“…In recent decades, China has experienced dramatic social and economic changes resulting in increased divorce rates, larger income gaps, and more migrant children attending schools in cities. Children from these diverse and disadvantaged backgrounds (e.g., lower income, divorced families) may be marginalized at school and perceived as different (Wang, Ni, Ding, & Yi, 2015). School psychologists and teachers should hold class meetings to discuss how to accept and appreciate individual differences among peers in order to promote respect towards diversity and reduce bullying.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent decades, China has experienced dramatic social and economic changes resulting in increased divorce rates, larger income gaps, and more migrant children attending schools in cities. Children from these diverse and disadvantaged backgrounds (e.g., lower income, divorced families) may be marginalized at school and perceived as different (Wang, Ni, Ding, & Yi, 2015). School psychologists and teachers should hold class meetings to discuss how to accept and appreciate individual differences among peers in order to promote respect towards diversity and reduce bullying.…”
Section: Discussionmentioning
confidence: 99%
“…School staff should also foster positive psychology traits among students, such as gratitude and optimism, in addition to preventing mental illness. Because many Chinese school psychological service providers teach mental health classes, they should incorporate school climate interventions and positive psychology interventions into those classes (Wang et al., 2015). They can engage students in class meetings to identify the best way to foster positive school climate and discuss difficult topics related to bullying, such as dominance and popularity (Wang et al., 2013).…”
Section: Discussionmentioning
confidence: 99%
“…In a qualitative study [29] it was found that school psychologists may have an indirect role in enabling teachers' resilience by mitigating the school-related challenges faced by teachers. The need for counseling support for teachers was also recognized by another study [30], where approximately half of the participants reported that the school psychologists provided them with support/consultation approximately once a week. In general, this type of support includes, for instance, the following activities: (i) general counseling, (ii) teachers' development workshops, (iii) job stress management and (iv) addressing personal issues.…”
Section: Preferred Roles Of the School Psychologistsmentioning
confidence: 95%
“…Wang et al studied the role of guidance counselors in universities and colleges in China and stated that guidance counselors and teachers played an essential role in channeling students toward guidance and counseling services. However, insufficient research efforts are known whether students in universities of China are using guidance services accurately [3] . A study concluded that a lack of understanding of counseling is prevalent in the Chinese college environment; even the most knowledgeable populations in China, college professors, have limited knowledge of counseling services; as a result, professional counselors still have a long way to go in developing and promoting their mental health services [4] .…”
Section: Introductionmentioning
confidence: 99%